(3GdeSJLGO ef aYdGJ GdCLhGOs - (3GdeMSf Hf Ydj Hf eMeO Hf CHj Gdage OGhO GdJfhNj GdHUQj, CHh Ydj,J (B384 (3g` s ((3SdjeGf Hf MSjf GHf GdCejQ LGfe GdjTHcj s)
(3ChdgG (B:s
(3GdMeO ddg Pj GdLhO hGdcQe CeQJ CWGd Gddg aj GdfYeI YeQc Cf CLeY dc ef CNHGQ GdCLhGO CLhOgG s
(3BNQgG (B:s
(3bhdg JYGdi(B: "(3Edi HdmO de JchfhG HGdZjg EdG HTb GdCfoaS(B" (3aGSJMSf LhGHgG hSQJg hCeQ HTQGFgG, hMXjJ YfOg s
(3GdNQe Cced HNW MOjK cJHg eYjf GdOjf SfI (B1367(3g`` fbdkG Yf eUhQI ef fSNI Hhf HCdeGfjG hHChdgG JQLeI ddeUfa efbhdI ef hajGJ GdCYjGf dGHf NdcGfs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B288 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B185s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B58 s
Keywords: (3GdCOHs